Being 'really real' on YouTube: authenticity, community and brand culture in social media entertainment. Issue 1 (August 2017) - Cunningham, Stuart; Craig, David
This article develops an analytical framework to understand the modes of address of native-to-online content types (gameplay, do-it-yourself (DIY) beauty, personality vlogging). These types of content differ sharply from established screen entertainment and are constituted from intrinsically interactive audience-centricity and appeal to authenticity and community in a commercialising space which we call 'social media entertainment'. The article offers a revisionist analysis of the shaping and disciplining of brand culture through the twinned discourses of authenticity and community. The significance of social media entertainment lies in that, for a great many especially young viewers, this is what television is, now.